Developing an ESP digital platform based on students’ learning styles: A research study in ESP course design at a university English education study program - DewiNora Ronita; HartoyoIndra; NataliaChristine Helena; Batubara Khairunnisa Br. (Proceder: Applied Linguistics, Literature, and Language Education, 2025)
This research study aims to develop an ESP (English for Specific Purposes) Digital Platform tailored to students’ diverse learning styles. Applying Borg and Gall’s (1983) R&D approach, the research seeks to address the varying preferences of visual, kinesthetic, and auditory learners within the context of ESP Course Design. The study population consists of 50 students enrolled in ESP Course Design across six classes. Through a structured sampling method, students from each class were selected to represent the diverse demographics of the population. Utilising a mixed-methods approach, the research employed surveys and interviews to gather data on students’ learning preferences and experiences. The findings revealed that 54% of students prefer visual learning methods, 24% favour kinesthetic approaches, and 22% exhibit a preference for auditory learning modalities. Building upon these findings, the research aims to design and implement an ESP Digital Platform that caters to the identified learning styles. The platform will incorporate interactive visualisations, hands-on activities, audio lectures, and other multimedia resources to engage students and enhance their learning experience. By incorporating adaptive learning techniques and assessment tools, the platform aims to customise content delivery and evaluate students’ understanding across different learning styles. Additionally, it will prioritise accessibility and usability to ensure effortless navigation and interaction for all users. In summary, this study improves ESP education by providing actual proof of how students like to learn through a digital tool that suits their different needs and useful ideas to those who are willing to make this teaching better in ESP classes.